(untitled) - Greshes, Warren (Hoboken, New Jersey, 2012)
A practical guidebook to managing a stellar staff of high-achieversThe Best Damn Management Book Ever teaches managers, executives, and business owners how to create a staff of self-motivated, confident, high-achieving, self-starters. Acclaimed author of The Best Damn Sales Book Ever, Warren Greshes draws from years of experience to offer practical, easy-to-implement steps explained through entertaining, informative real-life stories. Learn to communicate more effectively with the people who report to you. The Best Damn Management Book Ever delivers actionable advice to hone your leadership skills. Install the self-starting generator in your people, enabling them to perform at a high level whether you're there or not Gain insight and determine each employee's "Hot Buttons" and motivators Correctly manage the three distinct groups that comprise every organization Delegate more effectively Use your time as a manager, executive, and business owner more efficiently Become the best damn leader your staff needs to achieve their goals and blow away the competition
Keywords: Động lực (Tâm lý học),Motivation (Psychology)